2015
DOI: 10.1016/j.neo.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and the Promise of Molecular Targeted Therapy in Malignant Gliomas

Abstract: Malignant gliomas are the most common malignant primary brain tumors and one of the most challenging forms of cancers to treat. Despite advances in conventional treatment, the outcome for patients remains almost universally fatal. This poor prognosis is due to therapeutic resistance and tumor recurrence after surgical removal. However, over the past decade, molecular targeted therapy has held the promise of transforming the care of malignant glioma patients. Significant progress in understanding the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 185 publications
0
94
0
11
Order By: Relevance
“…Despite the statistical improvement of current standard treatment with radiotherapy and temozolomide (TMZ) compared with radiotherapy alone, less than one third of patients survive beyond 2 years and cure is exceedingly rare (2). Therapies targeting particular altered gene products or signal transduction pathways have not provided durable responses in GBM likely due to multiple dynamic and interactive, compensatory, dysregulated pathways (3,4). Targeting multiple survival mechanisms in tumor can potentially avoid the development of adaptive resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the statistical improvement of current standard treatment with radiotherapy and temozolomide (TMZ) compared with radiotherapy alone, less than one third of patients survive beyond 2 years and cure is exceedingly rare (2). Therapies targeting particular altered gene products or signal transduction pathways have not provided durable responses in GBM likely due to multiple dynamic and interactive, compensatory, dysregulated pathways (3,4). Targeting multiple survival mechanisms in tumor can potentially avoid the development of adaptive resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most common malignant tumor in the central nervous system, with incidence rate of 5-7 per 100,000 and 5-year survival rate of approximately 20-30% (1). Gliomas originate from astrocytes, oligodendrocytes and neural stem cells or their precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Deep Biological Insight-Single cell proteomics technologies provide an important capability to study the high degree of cellular heterogeneity found in tumors (3,4) at a higher level of resolution, which is critical to understanding their resilience to therapy and to designing strategies for treatments that deal with the problem of recurrence (5). A microfluidics-based single-cell proteomic chip-the single-cell barcode chip-has demonstrated its usefulness in studying brain tumor cell models (6).…”
Section: Coordinated Analysis Of Single Cell Proteomics Data Formentioning
confidence: 99%